ANALISIS KEEKONOMIAN PROYEK KERJA ULANG (WORKOVER) SUMUR X LAPANGAN XD MENGGUNAKAN METODE PSC (PRODUCTION SHARING CONTRACT) - Selvia Sarungu'; Enosh Aksedurt Batistuta Losong; Firdaus Firdaus (PETROGAS: Journal of Energy and Technology, 2026)
Well X in the XD Field is a natural gas production well located in the XD field, South Sumatra, which is experiencing a decline in production caused by excess water production at a flow rate of 4 MMscfd and then repairs are carried out through rework, namely squeeze cementing. With the aim of the well producing gas optimally again. In a gas production volume of 1,095 Mmscf for 1 year of production from the “X” well, the result s of the calcu1ation of economic indicators at the time of planning on gas prices 5 USD/MMBTU obtained a net present value of 807 M US $, an internal rate of return of 379% and a payout time of 0.20 years based on the PSC (Production Sharing Contract) model.